2018
DOI: 10.3389/fnmol.2018.00274
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Binding of Mg2+ Over Ca2+ to CIB2 Triggers an Allosteric Switch Impaired in Usher Syndrome Type 1J

Abstract: Calcium and integrin binding protein 2 (CIB2) shares with the other members of the CIB family the ability to bind Ca2+ and Mg2+ via two functional EF-hand motifs, namely EF3 and EF4. As a cation sensor, CIB2 is able to switch to a conformation likely associated with specific biological functions yet to be clarified. Recent findings demonstrate the involvement of CIB2 in hearing physiology and a single, conservative point mutation (p.E64D) has been related to Usher Syndrome type 1J (USH1J) and non-syndromic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 49 publications
5
53
2
Order By: Relevance
“…In contrast to previous studies, Vallone et al (2018) showed that CIB2 is unable to function as a calcium sensor under physiological conditions due to a low affinity for Ca 2+ ions. However, they demonstrated that CIB2 does have a high affinity for Mg 2+ under the same conditions, and is therefore much more likely to function as a magnesium sensor (Vallone et al, 2018).…”
Section: Structurecontrasting
confidence: 98%
See 2 more Smart Citations
“…In contrast to previous studies, Vallone et al (2018) showed that CIB2 is unable to function as a calcium sensor under physiological conditions due to a low affinity for Ca 2+ ions. However, they demonstrated that CIB2 does have a high affinity for Mg 2+ under the same conditions, and is therefore much more likely to function as a magnesium sensor (Vallone et al, 2018).…”
Section: Structurecontrasting
confidence: 98%
“…A small number of mutations in CIB2 have been associated with USH1J, including a conservative point mutation, c.192G>C (p.E64D; Riazuddin et al, 2012). The E64 residue is in the N-terminal domain and is thought to communicate with the EF3 cation binding site in the C-terminal domain (Vallone et al, 2018). Therefore, mutations at this site prohibit this inter-domain communication, impairing the cation responsiveness of CIB2.…”
Section: Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Riazuddin et al reported a homozygous pathogenic variant of CIB2 in USH1 patients (50) which affected the function of CIB2 as a calcium sensor. Vallone et al later demonstrated that, in physiological conditions, CIB2 can function as a magnesium sensor and the variant described by Riazuddin et al affects this capacity (88). Studies show that knockdown of Cib2 in mice eliminates mechanotransduction in cochlear hair cells (89,90).…”
Section: Ultra-rare Ush Genesmentioning
confidence: 99%
“…The molecular weight and Stokes radius of all GCAP1 variants (20 µL injection volume at a concentration of 50 µg/µL) was estimated in the presence of 2 mM Ca 2+ , 3.5 mM Mg 2+ or 2 mM EGTA, according to refs. [51,52].…”
Section: Analytical Size Exclusion Chromatographymentioning
confidence: 99%